Bromate determination by X-Ray fluorescence (XRF) to identify pre-baking potassium bromate addition in bread - Perez, Roberto Daniel (2010)
Wavelength-dispersive x-ray fluorescence (WDXRF) was applied to determine bromate (Br) as an indication of pre-baking bromate addition in bread. The proposed methodology needed a minimum sample preparation procedure because it was carried out directly on solid samples. The calibration of Br in bread obtained showed low detection limit and high sensitivity to distinguish precisely Br concentrations greater than natural Br. The excellent performance of the present methodology would be useful to identify pre-baking bromation in bread, which can be used to help set up a programme to control bromation in bread. Application of this methodology to bakery control caused an important reduction of bromate use in province of Cordoba, Argentina.